PROTEIN RESIDUE (CIEP) ANALYSES OF SAMPLES FROM SITES HbRi-33, HaRk-8, HaRl-53, BRITISH COLUMBIA, CANADA - Cummings, Linda Scott (2020)
Site HbRi-33 overlooks Peace River and Halfway River to the west, lying approximately 1 km northwest of the confluence of these two rivers. A projectile point recovered from Level 2 was submitted for protein residue analysis. Site HaRk-8 is located approximately 60 km westsouthwest of Fort St. John in northeast British Columbia near the confluence of the peace River and Right Creek. A single scraper recovered from Level 2 was submitted for protein residue analysis. Site HaRl-53 overlooks the Peace River to the southwest and lies approximately 513 m north of the confluence of the Peace River the Maurice Creek. Two scrapers were submitted for protein residue analysis.